The Mediating Role of Brand Image in the Relationship between Viral Marketing and Repurchase Intention among Menantea Consumers in Bandung - Henny Utarsih; Nabila Cinta Putri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Digital platforms have reshaped competition in the food and beverage sector, making it increasingly important for brands to convert short-term online attention into sustained customer loyalty. This study investigates whether brand image explains how viral marketing translates into repurchase intention among Menantea consumers in Bandung, Indonesia. A quantitative, cross-sectional survey was conducted with 130 consumers who had previously purchased Menantea products and had encountered the brand's digital content. Respondents were selected purposively, and the data were examined through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4 with a 5,000-resample bootstrapping procedure. The results show that viral marketing significantly strengthens both brand image and repurchase intention. Brand image also has a positive effect on consumers' willingness to buy Menantea again. The indirect relationship is significant while the direct path remains significant, demonstrating partial mediation. Accordingly, widely shared content is more likely to support repeat purchasing when it also reinforces a distinctive, credible, and favorable perception of the brand. The study extends signaling theory and consumer behavior research by clarifying brand image as a mechanism that connects digitally circulated marketing messages with post-purchase intentions in an Indonesian beverage-brand setting. Managerially, the findings indicate that Menantea should combine authentic, interactive, and shareable content with consistent brand cues, dependable product quality, and responsive social-media engagement to cultivate longer-term customer relationships.